People of the book canon, meaning, and authority - Halbertal, Moshe (Cambridge Harvard University Press, 1997)
People of the Book offers an introduction to Jewish hermeneutics, and conveys the importance of the tradition to both general and academic readers.
Keywords: Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish. Bible. -- Old Testament -- Canon. Bible. O.T -- Criticism, interpretation, etc., Jewish -- Canon. Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish -- Canon. RELIGION -- Judaism -- Sacred Writings. Bible. -- Old Testament. Oude Testament. Canon. Jodendom